Dietary and metabolic reprogramming alleviates neurodegeneration: a review of mechanisms and clinical implications - Fang, Liyuan; Zhuang, Yafei; Zhang, Minli; Yang, Deqian; Zhang, Ruyi; Peng, Jusheng; Wang, Changhua (Frontiers in Nutrition, 2026)
Neurodegenerative diseases, characterized by their insidious onset and progressive neuronal degeneration, present significant challenges in the fields of neuroscience and medicine. We elucidate the critical role of nutrition and cellular metabolism in the pathogenesis and progression of these disorders, with a particular focus on Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington’s disease (HD). We demonstrate that fundamental nutrients such as glucose, lipids, and amino acids are crucial for neuronal bioenergetics, oxidative stress mitigation, and neuroprotective functions. Furthermore, we emphasize the concept of metabolic reprogramming as a key driver in neurodegeneration; this process entails alterations in energy metabolism, mitochondrial dysfunctions, and shifts in nutrient utilization that exacerbate neuroinflammation and oxidative stress. We emphasize the potential advantages of nutritional strategies, especially those involving the Mediterranean dietary pattern, characterized by high antioxidant and omega-3 fatty acid content, to optimize cellular metabolic pathways and attenuate disease manifestations. However, clinical application of nutritional strategies faces several challenges including complexities surrounding nutrient mechanisms, patient adherence issues, and concerns regarding long-term efficacy. To address these obstacles, we advocate for personalized nutrition approaches that integrate metabolomics, genomics, and epigenetics to tailor interventions according to individual metabolic profiles. Additionally, emerging strategies such as probiotics along with synergistic combinations of nutrients and pharmaceuticals offer promising avenues for enhancing therapeutic outcomes. In conclusion, understanding the intricate interplay between nutrition and cellular metabolism is crucial for developing effective treatments for neurodegenerative diseases. Future research should prioritize mechanistic studies alongside precise assessment tools as well as high-quality clinical trials to validate the efficacy of these interventions.